Plastische Graphik. - Fath, Manfred; Köllhofer, Thomas (Mannheim : Städtische Kunsthalle, 2000)
Bernhard, Franz ; Boezem, Marinus ; César ; Chillida, Eduardo ; Christo ; Cremer, Siegfried ; Cucchi, Enzo ; Dahmen, Karl Fred ; Erb, Leo ; Gabino, Amadeo ; Hagebölling, Wilfried ; Haypeter, Werner ; Holweck, Oskar ; Hüppi, Alfonso ; Jacobi, Ritzi ; Kissel, Rolf ; Klafki, Anja ; Kricke, Norbert ; Krieg, Dieter ; Lafranca, François ; Lind, Gerd ; Mon, Franz ; Reynolds, Alan ; Schönemann, Helga ; Schoonhoven, Jan ; Schultze, Bernard ; Serra, Richard ; Smith, Richard ; Stein, Peter ; Tyson, Ian ; Uecker, Günther ; Vasarely, Victor ; Warhol, Andy ; Wyss, Marcel
biog. p. 47-48
Duits
Plastische Graphik, Städtische Kunsthalle, Mannheim, 1. Juli bis 24. September 2000
boek